Efficiency of the Overlay Network Clustering based on the Locality Metric - Poryev, G.V. (Реєстрація, зберігання і обробка даних, 2011)
The method of estimating the efficiency of the overlay network clustering in the swarms of peer-to-peer networks is proposed. The brief overview of the locality metric as a topological distance substitute is given and using regional Internet registries as information sources for constructing the structural model of the network is substantiated.